Tailored-shear extrusion carbon nanofibre/polyamide composites and its effect on the electrical percolation threshold - Leer, C. (2006)
Carbon nanofibre (CNF) thermoplastic composites can offer permanent conductivity at electrostatic discharge levels with very low filler levels, without affecting processing and other beneficial properties of the host polymer. This capacity makes these materials of particular interest for, for example, electrostatically painted automotive parts. However, ultimate properties depend largely on the processing history of the material. The present paper describes a methodology to optimise the production of nylon 6 composites reinforced with CNFs by balancing fibre dispersion and fibre degradation during melt compounding. The optimisation approach used combines a modelling routine of the compounding process with a multiobjective evolutionary algorithm able to deal with multiple objectives simultaneously. The electrical properties of the composites, compounded and subsequently injection moulded at several fibre loadings, revealed direct relationships with the modelling optimisation parameters. In this way, the potential of tailoring operating conditions and/or screw design during compounding to obtain desired final product properties was demonstrated.